Recent advances in porous organic frameworks for sample pretreatment of pesticide and veterinary drug residues: a review. Issue 24 (16th November 2021) - Lin, Shumin; Zhao, Zhe; Lv, Yun-kai; Shen, Shigang; Liang, Shu-xuan
Abstract : The latest research on porous organic frameworks, as well as their multifunctional composites in the sample pretreatment for pesticide and veterinary drug residues, were comprehensively reviewed. Abstract : Rapid and accurate detection of pesticide and veterinary drug residues is a continuing challenge because of the complex matrix effects. Thus, appropriate sample pretreatment is a crucial step for the effective extraction of the analytes and removal of the interferences. Recently, the development of nanomaterial adsorbents has greatly promoted the innovation of food sample pretreatment approaches. Porous organic frameworks (POFs), including polymers of intrinsic microporosity, covalent organic frameworks, hyper crosslinked polymers, conjugated microporous polymers, and porous aromatic frameworks, have been widely utilized due to their tailorable skeletons and pores as well as fascinating features. This review summarizes the recent advances for POFs to be utilized in adsorption and sample preparation of pesticide and veterinary drug residues. In addition, future prospects and challenges are discussed, hoping to offer a reference for further study on POFs in sample pretreatment.